099 Safety and effectiveness of dimethyl fumarate in multiple sclerosis patients treated over 5 years. Issue 6 (27th May 2022) - Giles, Kathryn; Balashov, Konstatin; Macdonell, Richard; Windsheimer, Joerg; Okai, Annette; Martinez, Mikel; Mokliatchouk, Oksana; Lyons, Jennifer; Kapadia, Shivani
Abstract : Introduction: In clinical studies, delayed-release dimethyl fumarate (DMF) demonstrated a favorable benefit-risk profile in patients with relapsing-remitting multiple sclerosis (MS). Real-world studies enable char- acterization of risks that may emerge with long-term exposure in clinical practice. ESTEEM (NCT02047097 ) is an ongoing 5-year study characterizing real-world long-term safety and effectiveness of routinely pre- scribed DMF in MS patients. Methods: Patients treated with DMF were recruited from ~380 sites. The primary objective was to determine incidence, type, and pattern of serious adverse events (SAEs), and AEs leading to DMF discontinuation. Results: As of April 3, 2019, 5804 patients had ≥1 dose of DMF. SAEs were experienced by 245 (4.8%) patients, with infections (n=64; 1.3%) and nervous system disorders (n=35; <1%) the most common. There were 1676 (33.0%) permanent treatment discontinuations. Annualized relapse rate over the period of up to 5 years was significantly lower than in the year prior to baseline (risk reduction 88.6% [95% confidence interval: 87.7–89.4]; P<0.0001). Conclusions: These results reveal low risk of SAE and beneficial therapeutic effects over up to 5 years of real-world DMF use. Updated safety and efficacy results for DMF patients in the United Kingdom will be presented. Support.Biogen. Disclosures: Included on the poster. Ben.newth@biogen.com